General anaesthesia of indigenous pigs in Bangladesh (Bangladesh Veterinarian, 2014)
Anaesthetic trials were conducted with propofol (P), xylazine-propofol (XP), xylazine-ketamine (XK), xylazine-thiopentone (XT) in 16 healthy indigenous pigs. Respiration rate decreased significantly (P < 0.01) five minutes after induction, and during maximum depth of anaesthesia, and had not returned to control value after recovery from anaesthesia with all anaesthetic combinations. Heart rate with P increased significantly (P